Flash Sale Sebagai Indikasi Predatory Pricing pada Aplikasi E-Commerce Perspektif Hukum Persaingan Usaha - Komang Kory Jayani; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2022)
E-commerce services are currently implementing flash sale promos which are one of the marketing strategies by issuing discounts or discounts at certain times even reaching the price of nine hundred and ninety-nine rupiahs. This is an indication of Predatory Pricing which is prohibited in business competition law. This study aims to examine the setting of flash sales on E-commerce applications which are indicated as Predatory Pricing, and reveal law enforcement on Predatory Pricing actors who carry out flash sales on E-commerce applications. In this study using a normative research method with a Legislative approach. The legal materials used are primary and secondary legal materials. Library data collection techniques or library research related to flash sales practices as an indication of Predatory Pricing in E-commerce applications. The results of the study indicate that the provisions of Article 20 of Law Number 5 of 1999, that Predatory Pricing is not necessarily prohibited, but it must be proven that predatory pricing will result in unfair business competition, from this it can be seen that not all selling and loss activities is an unlawful act. The flash sale promo that is carried out by one of these E-commerce is not classified as Predatory Pricing, because it does not meet the requirements and elements of the act described in Law Number 5 of 1999 concerning unfair business competition